The effects of using mother tongue in delivering health protocol messages on health attitudes and behaviors: Do gender, age, and education level make any difference? - Fathiaty Murtadho (Indonesian Journal of Applied Linguistics, 2022)
This study aimed to investigate the effects of using the mother tongue in delivering audiovisual health protocol messages on health attitudes and behavior during the Covid-19 pandemic. The measurement of the investigation into the variables of gender, age, and education level relied on the use of a 2X2X4 factorial design. Following the design, this study involved 240 volunteer participants randomly selected from 34 provincial clusters in the Indonesian territory. The data on the participants’ health attitudes and behaviors were collected through an online questionnaire formulated on five (5) scales. The questionnaire was given to 240 participants as a sample group after receiving health protocol messages conveyed in their mother tongue in a video. The collected data were analyzed by using SPSS and an additional syntax design. The analysis shows that the use of the mother tongue in conveying health protocol messages simultaneously had a significant effect on changes in attitudes and behavior by attending to gender, age, and education levels as contributing factors to the study results. The significant impact on attitude was partially seen from gender and age level factors, while the considerable influence on behavior was seen from gender factors. The other important findings, such as the interaction between factors and the proposed concept of direct persuasive perlocutionary, were also discussed.